Multiplier flock scheme in Barbari goats: An entrepreneurship model for in situ breed conservation and improvement - SINGH, M K; POUROUCHOTTAMANE, R; KUMAR, AKHILESH; SINGH, S P; RANJAN, RAVI; DIXIT, A K; SHARMA, NITIKA; KUMAR, RAVINDRA (The Indian Journal of Animal Sciences, 2024)
Barbari is a most preferred breed for commercial goat farming-under intensive management. However, pure-bred Barbari goats; especially buck’s availability are meager due to indiscriminate castration which resulted in stagnation of genetic improvement and breed dilution. Multiplier Flock Scheme, an integrated genetic improvement model was initiated at ICAR-CIRG, Makhdoom to cater the need of pure-bred and high merit goats and to promote commercial goat farming. Trained farmers with adequate housing and know-how were registered under this scheme and they were provided a foundation stock of Barbari goat to multiply with all technical support. Currently, 50 such goat farms exist in India with flock size of 50 to 350 goats. Data was collected on animal performance and economic attributes from eight such farms. The least squares means of body weight of Barbari kids at birth, 3, 6, 9 and 12 months of age were 1.58, 7.22, 14.54, 20.01 and 25.76 kg, respectively. The average 60 and 90 days milk yield were 45.23 and 66.28 litre. The pre-weaning, post-weaning (3-12 month) and adult mortality were 9.03, 4.33 and 5.40% of flock strength. The net profit per goat/year ranged from ₹3800 to ₹13000 under various business models and the benefit:cost ratios ranged from 1.50 to 2.42 with mean and median value of 1.94 and 2.00, respectively. Present study concluded that multiplier flocks is efficient breeding model for improvement, conservation of goat breeds, promoting scientific goat farming at grass root level and very helpful to policymakers for small ruminant development.